2012
DOI: 10.1111/j.1948-7134.2012.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Aedes(Stegomyia)aegyptiandAedes (Howardina) cozumelensisin Yucatán State, México, with a summary of published collection records forAe. cozumelensis

Abstract: We collected mosquito immatures from artificial containers during 2010–2011 from 26 communities, ranging in size from small rural communities to large urban centers, located in different parts of Yucatán State in southeastern México. The arbovirus vector Aedes (Stegomyia) aegypti was collected from all 26 examined communities, and nine of the communities also yielded another container-inhabiting Aedes mosquito: Aedes (Howardina) cozumelensis. The communities from which Ae. cozumelensis were collected were all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Altitude ranges from 0 to 20 meters above sea level and human population size in our collection communities varied from 2,111 to 39,611. 2 For small-scale analysis, we obtained nested collections within Merida, Uman, and Caucel (Supplemental Figure 1). Five of these collections (comprising 232 mosquitoes) originated from the city of Merida (the largest urban center in the state), and were located within 3 km of each other (Supplemental Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altitude ranges from 0 to 20 meters above sea level and human population size in our collection communities varied from 2,111 to 39,611. 2 For small-scale analysis, we obtained nested collections within Merida, Uman, and Caucel (Supplemental Figure 1). Five of these collections (comprising 232 mosquitoes) originated from the city of Merida (the largest urban center in the state), and were located within 3 km of each other (Supplemental Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…In Yucatan State in Southern Mexico, Ae. aegypti is ubiquitous in large urban centers and in smaller communities 2 and dengue is hyperendemic. 3,4 The mosquito is controlled through a combination of physical source reduction (removal or alteration of potential water-holding containers) and use of insecticides including the organophosphate temephos to eliminate larvae from water-holding containers and since 2000 pyrethroids have been used to control adults in and around homes.…”
Section: Introductionmentioning
confidence: 99%
“…equinus , and Lim. durhamii were recorded previously in the Yucatán Peninsula (Najera-Vazquez et al 2004, Ortega-Morales et al 2010, García-Rejón et al 2012) but we present the first records of these species from Mérida City. Previous records from the Yucatán Peninsula for Toxorhynchites are restricted to Tx.…”
Section: Discussionmentioning
confidence: 47%
“…The studies reported on containers and seasonal patterns of abundance for immatures (Lloyd et al 1992; Winch et al 1992; Manrique-Saide et al 2008, 2012, 2013; García-Rejón et al 2011a; Arana-Guardia et al 2014; Baak-Baak et al 2014) and examined different indoor environments for adults (García-Rejón et al 2008, 2011b). Additional studies have reported more broadly on the mosquito fauna of the Yucatán Peninsula (Najera-Vazquez et al 2004, Zapata-Peniche et al 2007, Ortega-Morales et al 2010, García-Rejón et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation